2016
DOI: 10.1016/j.jechem.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanism of aqueous-phase conversion of γ-valerolactone (GVL) over a Ru/C catalyst

Abstract: The present work explores the reaction pathways of γ-valerolactone (GVL) over a supported ruthenium catalyst. The conversion of GVL in aqueous phase over a 5% Ru/C catalyst was investigated in a batch reactor operating at 463K under 500-1000 psi of H 2 . The main reaction products obtained under these conditions were 2-butanol (2-BuOH), 1,4-pentanediol (1,4-PDO), 2-methyltetrahydrofuran (2-MTHF) and 2-pentanol (2-PeOH). A complete reaction network was developed, identifying the primary and/or secondary product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 38 publications
5
29
0
Order By: Relevance
“…The low concentrations of 1,4-nonanediol suggested that it was also an intermediate, as reported elsewhere [36,37,44]. PTHF formed from 1,4-nonanediol [36,37,44] and reacted further on Ru/ ZrO 2 and Rh/ZrO 2 , as attested by its low concentration and the decrease in the latter part of its yield profile on these two metals. A HDO study of MTHF reports its conversion to 2-pentanone and 1-pentanol as primary products [45].…”
Section: Hdo Productssupporting
confidence: 67%
See 3 more Smart Citations
“…The low concentrations of 1,4-nonanediol suggested that it was also an intermediate, as reported elsewhere [36,37,44]. PTHF formed from 1,4-nonanediol [36,37,44] and reacted further on Ru/ ZrO 2 and Rh/ZrO 2 , as attested by its low concentration and the decrease in the latter part of its yield profile on these two metals. A HDO study of MTHF reports its conversion to 2-pentanone and 1-pentanol as primary products [45].…”
Section: Hdo Productssupporting
confidence: 67%
“…Analogously, the MTHF conversion in HDO on Ru/C has been reported to increase exponentially with respect to temperature, as expected from kinetics [43]. Furthermore, in the GVL literature with Ru/C, the temperature is kept low (190 °C) when high yields of 2-butanol [36] and MTHF [44] are desired.…”
Section: Hdo Productsmentioning
confidence: 71%
See 2 more Smart Citations
“…The authors have shown that the GVL ring-opening step through breaking the C(1)-O(2) bond ( Figure 10) proceeds rather easily with an activation energy of 25 kJ/mol and exothermicity (-31 kJ/mol), and the rate-limiting step is the hydrogenation step of the formed acyl intermediate CH 3 CH(O * )-(CH 2 ) 2 -C * -O * with an activation barrier of 146 kJ/mol and endothermicity (+74 kJ/mol) to yield 1,4-PDO. In contrast, the alternative pathway of GVL ring-opening through breaking the C(4)-O(2) bond ( Figure 10) proceeds with more difficulty with a much higher energy barrier of 122 kJ/mol, which leads to VA (Rozenblit et al, 2016). Aqueous-phase hydrogenations of GVL catalyzed by 5 wt.% Ru/C were carried out by Rozenblit et al (2016) at 200 • C under 69 bar dihydrogen pressure to obtain a conversion of GVL of 10.3 mol% and a spectrum of products with a yield of 4.95 mol% 2butanol, formed after C-C bond cleavage in a decarbonylation step of the surface acyl intermediate CH 3 CH(O * )-(CH 2 ) 2 -C * -O * obtained after GVL ring-opening, and further 4.63 mol% 1,4-PDO after hydrogenation of the acyl intermediate, 0.64 mol% 2-MTHF after dehydration of 1,4-PDO and cyclization, and 0.08 mol% 2-pentanol obtained after deoxygenation and further hydrogenation of the surface CH 3 CH(O * )-(CH 2 ) 2 -C * -O * acyl intermediate.…”
Section: Homogeneous Water-soluble Catalytic Complexesmentioning
confidence: 99%